1987
DOI: 10.1017/s0003356100036710
|View full text |Cite
|
Sign up to set email alerts
|

A genetic analysis of litter traits in Bauscat and Giza White rabbits

Abstract: An analysis of doe productivity traits was carried out on 884 litter records including 52 sires and 210 daughters (paternal half sisters) of Bauscat (B) and Giza White (G) rabbits. Traits examined included litter size and weight at birth and at weaning, pre-weaning mortality and mean weight of young at weaning. Year-of-kindling affected most litter traits but no pattern of parity effects on litter size and pre-weaning mortality was observed. Litter weight and mean weight of young at weaning generally increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0
2

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 14 publications
(18 reference statements)
5
20
0
2
Order By: Relevance
“…Similar findings were observed by many researchers (Khalil et al, 1987;Afifi et al, 1992;El-Raffa, 1994). The higher values of genetic correlations between litter size traits indicate that these traits were controlled by the same genes.…”
Section: -Genetic Parameterssupporting
confidence: 90%
See 1 more Smart Citation
“…Similar findings were observed by many researchers (Khalil et al, 1987;Afifi et al, 1992;El-Raffa, 1994). The higher values of genetic correlations between litter size traits indicate that these traits were controlled by the same genes.…”
Section: -Genetic Parameterssupporting
confidence: 90%
“…The estimates of genetic parameters for rabbit populations raised under tropical or subtropical conditions, using recent methods of statistical analysis such as REML, animal models and large data sets are limited (Ferraz and Eler, 2000). Khalil et al (1987) concluded that the potential for genetic improvement is largely depended on the heritability of the trait measured and its relationship with other traits of economic importance. Elamin et al (2011) reported that Heritability, which is a function of variance components, provides information about the genetic nature of a trait and is needed for genetic evaluation and selection strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Rabbit producers are interested in the relationship that exists between body weight and physical characteristics, since this reflect performance of the rabbits. According to Khali et al [3] breeders need to sure of the relationship that exists between these parameters and to organize the breeding programmes so as to achieve an optimum combination of body weight and good conformation for maximum economic returns. Relating body weight to linear body measurements is a way of predicting body weight of rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential for rabbit breeders to establish the relationship that exists between life weight and linear measurements as well as to organize the breeding programmes, so as to achieve an optimum combination of body weight and good conformation for maximum economic returns [3]. This makes the work of the breeders easier and faster as its effects can then be concentrated on traits that are easier to measure.…”
Section: Introductionmentioning
confidence: 99%
“…A eficiência desse processo é dependente da precisão com que são obtidas as estimativas dos componentes de (co)variância das características usadas como critérios de seleção (MARTINS et al, 1997). Os métodos usados para a estimação dessas (co)variâncias já estão bem definidos (GIANOLA; FERNANDO, 1986) e as estimativas podem variar de acordo com a população e com o ambiente em que os indivíduos são criados.…”
Section: Introductionunclassified